A Survey of Weeds of Rangelands of Western Rajasthan - Samraj, P (Annals of Arid Zone, 2016)
A survey of weeds flora was made during 1968 and 1969 on ten paddocks selected at random in Sojat Unit of the Central Arid Zone Research Institute,Jodhpur. 146 species belonging to 100 genera and 36 families are enumerated in this paper. Compositae and Papilionaceae were the two most dominant families with 17 species each.